Toponymy of Street Name Changes in Gorontalo City: An Anthropolinguistic Approach and its Contribution to Indonesian Language Learning - Sri Justevani; Dakia N Djou; Asna Ntelu (Universitas Islam Negeri Palopo, 2026)
Street naming, as part of odonymy studies, does not merely serve as a geographical marker but also represents history, cultural identity, and collective memory of the community. Although various studies on toponymy have been conducted, research specifically addressing street name changes in Gorontalo City from an anthropolinguistic perspective and their implications for Indonesian Language learning remains limited. This study aims to describe the relationship between street name changes and socio-cultural identity, analyze street name changes from a toponymy perspective, and explain their contribution to Indonesian Language learning. The study employs a descriptive qualitative method using observation, interview, and documentation techniques. Results show that street name changes in Gorontalo City are dominated by eponymic naming that uses names of national heroes, local figures, royal figures, and other influential persons. The change from Jalan Merdeka to Jalan Taki Niode and from Jalan Usman Isa to Jalan Raja Eyato reflects efforts to preserve local history and strengthen the cultural identity of the Gorontalo community. From an anthropolinguistic perspective, street names function as a medium for representing cultural values, collective memory, and reverence for figures of merit. The findings also indicate that toponymy studies can be utilized as contextual learning resources for biography texts, descriptive texts, and local culture-based literacy projects in Indonesian Language learning. Thus, street name changes are not merely administrative in function but also play a role in preserving cultural identity and developing education based on local wisdom.